2021
DOI: 10.1097/as9.0000000000000065
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection for Hepatocellular Carcinoma in Nonalcoholic Fatty Liver Disease

Abstract: Structured summary2 Provide a structured summary including, as applicable: background; objectives; data sources; study eligibility criteria, participants, and interventions; study appraisal and synthesis methods; results; limitations; conclusions and implications of key findings; systematic review registration number. INTRODUCTIONRationale 3 Describe the rationale for the review in the context of what is already known.Objectives 4 Provide an explicit statement of questions being addressed with reference to par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 74 publications
1
8
1
Order By: Relevance
“…The finding of similar OS and RFS between the two groups of patients contrasts with the significantly higher survival reported for patients with NAFLD- or MAFLD-related HCC in two previous meta-analyses involving 7226 17 and 5579 patients respectively 18 . The present results may be more reliable because the sample is substantially larger (11 477 patients) and the inclusion criteria are more stringent.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…The finding of similar OS and RFS between the two groups of patients contrasts with the significantly higher survival reported for patients with NAFLD- or MAFLD-related HCC in two previous meta-analyses involving 7226 17 and 5579 patients respectively 18 . The present results may be more reliable because the sample is substantially larger (11 477 patients) and the inclusion criteria are more stringent.…”
Section: Discussioncontrasting
confidence: 94%
“…It is not clear whether these differences translate into a different prognosis after hepatic resection. Two meta-analyses have evaluated the safety and prognosis of hepatic resection for treating NAFLD-related HCC 17 , 18 , but they included relatively few original studies, and several relevant studies have been published since then 19–22 . Moreover, the meta-analyses were less rigorous in their inclusion criteria, such that some patients in the observation group did not meet diagnostic standards for NAFLD-related HCC 23–28 , and some patients received palliative treatment instead of resection 29–33 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the sample size was small, these findings generate the hypothesis that background etiology may impact the risk of recurrence and mortality after resection. Similar findings have been demonstrated in resected MAFLD-HCC in a recently published metanalysis [ 28 , 29 ]. In our case, a potential explanation is that patients tend to be more adherent to medical treatment and lifestyle changes after the diagnosis of CCA, and it would minimize the carcinogenic effect of overweight and altered glucose metabolism in the follow-up.…”
Section: Discussionsupporting
confidence: 89%
“…This outcome might be related to the higher proportion of patients with NAFLD-related hepatocellular carcinoma without cirrhosis, as cirrhosis increases the risk of hepato cellular carcinoma recurrence after resection. 46,47 Several studies have reported improved outcomes in NAFLD-related compared with non-NAFLD-related hepato cellular carcinoma, 48,49 although there have also been reports of more advanced disease at presen tation and poorer outcomes for NAFLD-related hepato cellular carcinoma. 14,50 These conflicting results could have arisen from previous studies being specific to a country, region, or treat ment, hence limiting their generalisability.…”
Section: Discussionmentioning
confidence: 99%